Penggunaan Daun Afrika (Vernonia amygdalina) dalam Menurunkan Kolesterol Guna Meningkatkan Permintaan Daging Itik Lokal Sumatera Barat - Suhaemi, Zasmeli; Annisa, Indah Febrina; Aisyah, Aisyah (Department of Agribusiness, Halu Oleo University, 2021)
Cattle that have high body weight and low cholesterol production will improve the quality of local male duck meat products in West Sumatra. The purpose of this study was to see the response of local ducks, especially male ducks that were given African Leaf Flour in their rations, to body weight and blood cholesterol content. Because the cholesterol content of foodstuffs greatly determines consumer demand. This research was conducted from 12 September 2020 to 24 December 2020. The treatment that will be given is the use of African Leaf Flour of 5 levels (0%; 0.5%; 1.0%; 1.5% and 2.0%). To see the effect of the treatment, an experimental design was used, namely CRD (completely randomized design), each of which was repeated four times. The sample used was 80 male ducks kept for six weeks (4-10 weeks). The study results illustrate that the increase of African Leaf Flour given will increase the body weight gain (PBB) of ducks, with an increase in PBB of 23.59% in the use of African Leaf Flour 2.0%. Likewise, the Feed Conversion Ratio (FCR) was significantly better (P0.05). Meanwhile, blood HDL content tended to increase along with the increase in the provision of African Leaf Flour. The use of African Leaf Flour up to a level of 2.0% can improve the quality of local duck meat because it results in higher meat production and improves cholesterol content to create a healthy source of animal food, thereby reducing consumer hesitation to consume.